2005
DOI: 10.1007/s11746-005-1109-y
|View full text |Cite
|
Sign up to set email alerts
|

Solvent optimization for efficient enzymatic monoacylglycerol production based on a glycerolysis reaction

Abstract: This study was aimed at screening solvent systems of varying polarities to identify suitable solvents for efficient and practical enzymatic glycerolysis. Several pure solvents and solvent mixtures were screened in a batch reaction system consisting of glycerol, sunflower oil, and Novozym ® 435 lipase. Out of 13 solvents tested, tert-butanol and tert-pentanol were the only pure solvents suitable for a fast glycerolysis reaction with an acceptably high formation of MAG. In these systems, MAG contents of 68-82% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 21 publications
2
79
0
14
Order By: Relevance
“…Damstrup et al (Damstrup, Jensen, Sparsø, Kiil, Jensen, & Xu, 2005) evaluated various solvents and concluded that the highest MAG yield by glycerolysis were obtained with tertiary alcohols, tert-butanol (TB) and tert-pentanol (TP). The relatively low log P value of these tertiary alcohols (0.35 and 0.89, respectively) indicates both hydrophilic and hydrophobic characteristics, ensuring miscibility of the reactants.…”
Section: Introductionmentioning
confidence: 99%
“…Damstrup et al (Damstrup, Jensen, Sparsø, Kiil, Jensen, & Xu, 2005) evaluated various solvents and concluded that the highest MAG yield by glycerolysis were obtained with tertiary alcohols, tert-butanol (TB) and tert-pentanol (TP). The relatively low log P value of these tertiary alcohols (0.35 and 0.89, respectively) indicates both hydrophilic and hydrophobic characteristics, ensuring miscibility of the reactants.…”
Section: Introductionmentioning
confidence: 99%
“…5. Glyceryle monooleaate has many uses including preventing cardiovascular disorders by donating unsaturated fatty acids [38,43,44]. 6.…”
Section: Uses and Applications Of Glyceridesmentioning
confidence: 99%
“…According to Damstrup et al (2005), tert-butanol and tert-pentanol resulted in excellent solvents to carry out these reactions. Their log P values (0.35 and 0.89, respectively) indicate both hydrophilic and hydrophobic characteristics.…”
Section: Introductionmentioning
confidence: 99%